Mapping Intellectual Structure in General Management Studies Using VOSviewer - Judijanto, Loso (West Science Business and Management, 2025)
This study explores the intellectual terrain of general management research using bibliometric research and visualization techniques with VOSviewer. Drawing on data obtained from the Scopus database between 2000 and 2025, examination graphed co-citation, co-authorship, and keyword co-occurrence networks to unveil the topical structure of the field. The results indicate that the concept of the general manager serves as the hub node linking multifarious clusters of research, ranging from leadership and strategic management to talent management and career development, sustainability, and employee job satisfaction. The visualization reflects both the continuity of traditional concerns—leadership development, globalization, and strategic direction—and the aggregation of new ones like competencies, sustainability, and organizational well-being. These findings bear witness to the multidisciplinary nature of management scholarship, bridging human capital, strategic leadership, and global responsibility. The book enhances management literature through the presentation of an replicable and systematic intellectual mapping of the domain, which will serve as a valuable handbook for researchers, practitioners, and policymakers to harmonize their agendas with evolving knowledge patterns.